Adaptation Actions in Africa: Evidence that Gender Matters - Twyman, Jennifer; Green, Molly; Bernier, Quinn; Kristjanson, Patricia M.; Russo, Sandra; Tall, Arame; Ampaire, Edidah L.; Nyasimi, Mary; Mango, Joash; McKune, Sarah; Mwongera, Caroline; Badiane Ndour, Ndèye Yacine (2014)
This paper presents the initial data analyses of the CCAFS gender survey implemented in four sites in Africa. Using descriptive statistics we show gender differences in terms of perceptions of climate change, awareness and adoption of climate smart agricultural (CSA) practices, and types and sources of agro-climatic information in the four sites.We find that both men and women are experiencing changes in long-run weather patterns and that they are changing their behaviours in response; albeit relatively minor shifts in existing agricultural practices. For example, the most prevalent changes reported include switching crop varieties, switching types of crops and changing planting dates. As expected, women are less aware of many CSA practices. Encouragingly, this same pattern does not hold when it comes to adoption; in many cases, in East Africa in particular, women, when aware, are more likely than or just as likely as men to adopt CSA practices. In West Africa, overall, the adoption of these practices was much lower. In addition, we see that access to information from different sources varies greatly between men and women and among the sites; however, promisingly, those with access to information report using it to make changes to their agricultural practices. Our findings suggest that targeting women with climate and agricultural information is likely to result in uptake of new agricultural practices for adaptation.